Anatomy and Symbiosis of the Digestive System of the Vent Shrimp Rimicaris Exoculata and Rimicaris Chacei Revealed Through Imaging Approaches - Guéganton, Marion; Rouxel, Ouafae; Durand, Lucile; Cueff-Gauchard, Valérie; Gayet, Nicolas; Pradillon, Florence; Cambon-Bonavita, Marie-Anne (Frontiers in Marine Science, 2022)
The shrimp Rimicaris exoculata and Rimicaris chacei are visually dominant fauna co-occurring at deep-sea hydrothermal sites of the Mid-Atlantic Ridge (MAR). Their co-existence was related to contrasted life-history traits, including differences in their diet and reliance on chemoautotrophic symbionts at the adult stage. Both species of shrimp are colonized by diversified chemosynthetic symbiotic microbial communities in their cephalothoracic cavity. Symbiotic association with bacteria was also evidenced in their digestive system, and the major lineages were identified through sequencing (with Mycoplasmatales in the foregut and Deferribacteres in the midgut) but their precise distribution within each host species was not assessed. For the first time, we used Fluorescence in situ Hybridization (FISH) to visualize these lineages and describe their association with digestive structures of their host. The aim of the study was to identify possible differences between host species that could be related to their different life-history traits. For this purpose, we developed new specific FISH probes targeting Deferribacteres and Mycoplasmatales lineages identified in the digestive system of these shrimp. Our FISH results showed a partitioning of the bacterial lineages according to the digestive organ corroborating sequencing data, and highlighted their association with specific anatomical structures. Despite morphological differences between the foreguts of R. exoculata and R. chacei that could be related to the adult diet, our FISH results showed overall similar distribution of digestive symbionts for the two host species. However, a more comprehensive study is needed with specimens at different life or molt stages to reveal potential host specific patterns. Such comparisons are now possible thanks to our newly designed FISH probes. The tools used in our study are valuable for tracking symbiont lineages in the environment, allowing a better understanding of their relationship with their host along its life cycle, including their acquisition mechanisms.